Environmental Impact of Gold Mining Activities and Sustainable Mitigation Approaches: Case Study of Ilesa Surrounding areas, Osun State, Nigeria - Adegboyega L. ALUKO; Ayodeji T. BALOGUN (FUDMA Journal of Engineering and Technology, 2026)
Artisanal and small-scale gold mining (ASGM) has intensified markedly in Ilesa and nearby communities in Osun State, Nigeria, over the last decade. Although these activities sustain livelihoods and stimulate local economies, they increasingly generate serious environmental and public health concerns. This study provides a comprehensive evaluation of mining-related impacts using an integrated field–laboratory framework that combines soil analysis, surface water quality assessment, and satellite-based vegetation monitoring through the Normalized Difference Vegetation Index (NDVI). The approach incorporates both empirical field measurements and a structured dataset reflecting realistic contamination patterns, offering a reproducible model for environmental assessment in data-scarce regions. Soil samples collected from active and abandoned mining sites were analyzed for arsenic (As), lead (Pb), mercury (Hg), cadmium (Cd), and chromium (Cr). Concentrations of these metals were significantly higher near mining zones than in control locations, frequently exceeding international safety thresholds. Spatial analysis revealed clustering of arsenic and lead, forming contamination hotspots associated with elevated ecological and human health risks. Water samples obtained downstream of mining operations exhibited degraded quality, including reduced dissolved oxygen, elevated total dissolved solids and turbidity, and altered pH levels. These changes are consistent with acid generation, sediment displacement, and metal leaching from disturbed soils and mine tailings. NDVI analysis spanning 2010 to 2024 indicates a steady decline in vegetation cover and health within mined areas, confirming progressive land degradation and habitat loss. The study highlights strong linkages between mining intensity, environmental contamination, and ecosystem disruption. Risk pathways identified include direct soil contact, ingestion of contaminated water, and consumption of crops grown in polluted areas, suggesting significant long-term health implications. To address these challenges, the study proposes targeted interventions, including formal regulation of ASGM activities, mercury reduction, improved waste management, ecological restoration, community-based monitoring, and alternative livelihood programs. These measures aim to mitigate environmental damage, promote ecosystem recovery, and enhance sustainable resource governance.